Enhance well-being through social emotional learning at school: Study literature review - Romadhianti, Rona; Sunyono, Sunyono; Hariri, Hasan; Setiyadi, Ag. Bambang (Universitas Ahmad Dahlan, 2024)
In the industrial era 4.0, students as an important part of the education system, face various conflicts and problems that they bring to school. This implies that students need to overcome challenges that are not only limited to academic matters, but also pay attention to psychological aspects that are equally important. In such situations, social-emotional learning is the right solution. With this approach, students are not only proficient in skills, but also able to deal with psychological problems such as communication skills and emotional management. This research utilizes the Systematic Literature Review (SLR) method to investigate various research results and sources related to Social-Emotional Learning (PSE) activities. through language teaching. Of the 130 research journals there are 69 relevant research journals. Sixty-nine of these articles identified knowledge gaps in previous research, some of which have not touched on the school level and are still very minimal at the learning level. Therefore it is worth digging deeper.This article discusses the scope of Social-Emotional Learning (PSE).